Nilai-Nilai Agama Islam dalam Tradisi Bhuju’ Malem - Lailatur Rohmah; Nor Hasan (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
The tradition of bhuju' malem or ju'aji is a unique tradition in Karanganyar village that is still carried out today. This tradition is carried out as a form of respect for ancestors, an expression of gratitude for Allah's blessings. It reflects Islamic values and an effort to maintain local cultural identity in this modern era. The purpose of writing this article is to reveal the Islamic religious values contained in this tradition and introduce this tradition. This research method uses a qualitative approach with phenomenology and data collected through observation, interviews, and documentation techniques. The results of this study indicate that the bhuju’ malem tradition contains Islamic religious values, namely the value of worship in this tradition is reflected in the activities of reading the Qur’an, tahlil, and prayers together, sharing food, and strengthening ukhuwah Islamiyah. Therefore, this unique tradition is preserved and maintained to protect it from the rapid flow of globalization, which can dilute the authenticity and value of culture. This research will provide scientific information about Islamic values contained in local traditions and provide awareness to the community to continue preserving local culture.